Pneumotoxicity and hepatotoxicity due to Crotalaria pallida in the subchronic intoxication model in sheep - Jaramillo-Hernández, Dumar Alexander; Tamayo Rojas, Doris Juliette; Cifuentes Sánchez, Diana Consuelo [UNESP]; Veloza Angulo, Luis Carlos; Molina Diaz, Víctor Manuel; Pedraza Castillo, Luz Natalia; Roque Rodriguez, Anita Isabel (Universidad Nacional Mayor de San Marcos, Vicerectorado de Investigacion, 2021)
The aim of this study was to evaluate the potential for subchronic intoxication of Crotalaria pallida in sheep. Six rams were used, fed with hay and drinking water ad libitum, and 200 g/animal/day of commercial balanced ration. The sheep were distributed into a control group (G1) with two animals and an experimental group (G2) with four animals. In the G2 diet, 8 g of dry matter (DM) of C. pallida per kilogram of body weight were included for 28 days. All animals were clinically evaluated every 24 h. Animals were weighed and blood samples were taken for hemogram and liver and kidney profile on days 0, 14 and 28 post-exposure to C. pallida. All animals were slaughtered at the end of the study and samples were collected for histopathological analysis. No significant differences were found between groups with respect to clinical examination, hemogram data and blood chemistry; however, the histopathological study showed moderate thickening of the alveolar septa in the lung, severe vacuolar change in the liver, and moderate proteinuria in the kidney in the animals exposed to C. pallida.
Neumotoxicidad y hepatotoxicidad por Crotalaria pallida en el modelo de intoxicación subcrónica en ovinos
Keywords: Monocrotaline; Pyrrolizidine alkaloids; Toxic plants; Toxicity